IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PEMBANGUNAN PENDIDIKAN PADA DAERAH KEPULAUAN KECAMATAN LAONTI KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Syaifudin Suhri Kasim (Halu Oleo University, 2022)
This study aims to determine and analyze the implementation of local government policies in education development in island areas. This type of research uses case studies. The design of this case study by placing Laonti Subdistrict as the setting (place), object (actor), and event (activity) implementation of these policies. An informant is a subject who is considered capable of providing information on the problem under study. This research data collection technique is through observation, document studies, and interviews. Data analysis in this study was carried out during the data collection lasting until the moment of drawing conclusions. The results showed that there are five local government policies as a form of intervention against the problem of low quality of education and uneven distribution of services, namely: (1) construction of new school units in the form of opening one-stop elementary-junior high schools, (2) increasing teacher professionalism, (3) curriculum design & local content, (4) increasing community participation through school and community-based management, as well as (5) empowering the UPTD Office of the Laonti Sub-district Education Office. The implementation of government policies, in general, has not been running optimally. Because in dealing with education in island areas with the complexity of the problems in it, a special approach or special policy is needed by paying more attention to geographical factors.